China’s perspective on Shougang Hierro Perú. The 1990s - Li, Boya (2023)
Shougang Hierro Perú is the first investment made by a Chinese mega company in Latin America, marking the beginning of the expansion of the Asian power in this distant continent. This article aims to explain the reasons that contributed to the acquisition of Hierro Perú by the Chinese state-owned company Shougang and the reasons that generated its problems after 1995. Among others, the conflict with the workers and the political and social changes both in the Asian country and in the company itself. By researching Chineselanguage sources, it is concluded that the acquisition of Hierro Perú by Shougang was closely linked to China’s internal political transformation and is a unique product of the time when China began to explore the path of expanding its presence and influence in the world.